Pedometers and Aerobic Capacity: Evaluating an Elementary After-School Running Program. (2nd March 2014) - Wanless, Elizabeth; Judge, Lawrence W.; Dieringer, Shannon T.; Bellar, David; Johnson, James; Plummer, Sheli
Abstract : Childhood obesity affects 1 of every 6 youth in the United States. One contributing factor to this statistic is a lack of physical activity (PA). Demands related to accountability which are placed on educators to demonstrate academic achievement often result in resistance to allocating time during the school day for PA. One possible solution is to consider utilizing time after school to integrate PA programs. The purpose of this study was to assess the impact of a 12-week after-school pedometer-focused PA program on aerobic capacity and to examine the relationship between step count and aerobic capacity in elementary school aged children. A group of elementary students (n = 24 ; 9.5 ± 0.9 years) participated in a 12-week pedometer-focused PA program that included pretraining and posttraining fitness testing via the 20-meter version of the PACER test. Paired sample t -tests revealed significant differences between the pretest ( M = 21.0 laps, S D = 9.9 ) and posttest ( M = 25.2 laps, S D = 12.2 ) scores ( t = 4.04,   P ≤ 0.001 ) . A Pearson correlation revealed no significant relationship between individual step count and the difference between PACER pre- and posttest ( r = 0.318,   P = 0.130 ) . The program improved aerobic capacity, but an increase in pedometer-calculated step count was not a predictor.